Equilibrium real interest rates and secular stagnation: An empirical analysis for euro-area member countries - Ansgar Belke; Jens Klose (Research On Money in the Economy (ROME), 2017)
Is secular stagnation - a period of persistently lower growth such as that seen following the financial crisis of 2008/09 - a valid concern for euro-area countries? We tackle this question using the well-established Laubach-Williams model to estimate the unobservable equilibrium real interest rate and compare it to the actual real rate. In light of the considerable increase in heterogeneity among EU member countries since the beginning of the financial crisis, we apply our approach to twelve euro-area countries to provide country-level answers to the question of secular stagnation. The presence of secular stagnation in a number of euro-area countries has important implications for ECB decision-making (i.e., voting power in the Governing Council) and EU governance. Our results indicate that secular stagnation is not a significant threat to most euro-area countries, with one possible exception: Greece.
Keywords: E43; F45; C32; 330; equilibrium real interest rate; secular stagnation; euro-area countries; heterogeneity